Simulation Analysis of Uncoated Tungsten Carbide in Turning Process for AISI 1045 Carbon Steel - Benedict, Benny; Mahmod, Muhammad Faisal (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Turning operation is a very common machining process in industry and experimental trial and observation are widely used for the optimization process of setup parameters, which are expensive and time consuming. The objectives of this study are to simulate two dimensional cutting tool wear of uncoated tungsten carbide (WC) in turning process for AISI 1045 carbon steel using finite element method and to determine the effect of stress, strain, and temperature to the changes of cutting tool edge radius. DEFORM-2D FEM software is employed to assist the simulation process where rounded edge cutting tool is used and assumed as rigid body and the work piece is prescribed as thermo-plastic material. The results for tool wear rate and tool wear depth, there was significant increase of 13.69 mm/sec of 57% and 0.0052 mm of 36.4% respectively as when the tool edge radius increased from 0.05 mm to 0.15 mm. Next, value for strain, stress and temperature also increased with the value of tool edge radius, where 3.63 mm/mm, 30 MPa, and 320˚C respectively. These results shows that wear of cutting tool effect the machining process and a better understanding in FEM wear simulation is important in order to improve the turning machining process.